Análisis retórico del esténcil o estarcido (2012)
During this debate, I will try and answer the following questions: Can a rhetoricspeech be expressed by means of an image? If it were possible, howcan this image persuade an auditory? These questions arise from the imageof a stencil called Disney War, which appeared on the walls of many citiesworldwide, including Medellin and is being promoted or exposed throughthe Internet.